Pengaruh FED Rate, Inflasi, dan Indeks Dow Jones terhadap IHSG di Indonesia Periode 2022-2023 - Wahbi, Abdul Azim; Syahid, Syahid; Sahrudin, Sahrudin (Universitas Indraprasta PGRI, 2024)
This study seeks to examine the impact and evolution of the following factors on the Composite Stock Price Index (IHSG): Fed Rate, Inflation in Indonesia, and the Dow Jones Index. Bank Indonesia, Investing.com, library databases, scholarly publications, and other secondary sources provided the data used in this study. In this study, the data was analyzed using the Ordinary Least Square (OLS) method of multiple linear regression. The data was processed using software and covers the research period from January 2022 to December 2023. The data was sourced from various sources, including the internet, scientific journals, and books. This study found that although the Federal Funds Rate variable does not affect the IHSG at all, inflation does, and the Dow Jones Index does affect the Dow Jones Index. At the same time, the IHSG is affected by all of the factors at the same time.